A manifestação do fantástico nos contos “A escada”, “O pagão” e “Iluminuras”, de Natércia Campos - Magalhães Neto, Francisco Roque (2023)
The fantasy brings in its essence a disruption of the established rational everyday reality. Although it has achieved a certain international prestige, in our country, this type of fiction is generally put in the background by critics: since the 19th century, few authors have managed to establish their name from this type of literature, while others have fallen into oblivion for the expert criticism. In contemporary times, one of these writers is Natércia Campos, from Ceará, who dedicated most of her works to writing texts that dialogue with the fantastic, by creating a universe - often countryside - that is crossed by popular religiosity, with its rites , mysteries and hauntings that are typical of the social imaginary. Thus, this master's dissertation aims to analyze how the fantastic narrative of the short stories "A Escada", "O pagao" and "Iluminuras", present in the collection of short stories Iluminuras, is constructed. For this, we will analyze the various proposed theories that try to define and point out the elements that characterize the fantastic, focusing especially on the works of Tzvetan Todorov (2010), Felipe Furtado (1980) and Remo Ceserani (2006). From the theoretical body analyzed, we seek to identify how the author from Ceará created the fantastic effect in her narratives, her themes, the role played by the characters and by the narrative space. Thus, with the results obtained in this work, we point out that the fantastic elements used in these narratives come from the northeastern interior popular culture, creating an isolated narrative space, controlled by the official religion, but crossed by the religiosity of popular expression.